Reading and language skills book (stage 2) - Caton, Kate (Heinemann Oxford, 1998)
A reading and language skills book typically aims to enhance literacy by developing key competencies in reading comprehension, vocabulary, grammar, and writing. It often includes exercises on phonics, word recognition, sentence structure, and the interpretation of texts. The book is designed to build fluency in reading, strengthen language comprehension, and foster the ability to express ideas clearly in written and spoken language. It may also integrate activities like reading passages, answering questions, and writing prompts to encourage active learning and application of skills. Suitable for learners at different levels, the book seeks to improve overall communication abilities.